Crystallization behavior of random ethylene-butene copolymers modified with organic peroxide - Pérez, Claudio Javier (2012)
The effect of molecular cross-linking on the crystallization of random ethylene-1-butene copolymers obtained from hydrogenation of model polybutadiene was studied by means of differential scanning calorimetry. The copolymers were modified with different concentrations of organic peroxide in the molten state to generate different crosslink levels. Under isothermal conditions, the crystallization rate of the modified polymers decreased with the average molecular weight likewise to that observed in the unmodified copolymers. Original and modified polymers show similar isothermal crystallization rates when compared to equivalent weight average molecular weights. Under no isothermal crystallization conditions, the temperature and the enthalpy of crystallization of the modified polymer decreased almost linearly with the concentration of peroxide. The activation energy for crystallization increased with the concentration of peroxide indicating that the increment in molecular crosslinking restricts the crystallization process.